Exploring the level and sources of stress among international students in an Iranian university - Tajvar, Maryam; Atashbahar, Omolbanin; Ahmadizadeh, Elahe; Shaqura, Iyad (Journal of International Students, 2024)
Student life stress, characterized by mental pressure arising from the university life demands, is a significant concern. We aimed to investigate stressors faced by students and their coping mechanisms within an Iranian university. Using a cross-sectional design in 2021, we selected 165 international students through simple random sampling. Data were collected using a standardized student life stress questionnaire. The mean score of students' stresses was (63 ± 17), with self-imposed stress being the most prevalent stressor (64%), while conflict was the least prevalent (44%). When examining students' reactions to stressors, the mean score was (64 ± 21), with cognitive reactions being the most common response (68%) whereas behavioral reactions were the least common (38%). There was no significant relationship between students' stress levels and their demographic characteristics. Overall, our study highlights the need for culturally sensitive and tailored support programs for international students, as most participants experienced moderate stress.